Effectiveness of a clinic-based randomized controlled intervention for type 2 diabetes management: an innovative model of intensified diabetes management in Mainland China (C-IDM study). Issue 1 (26th February 2020) - Lou, Qinglin; Ye, Qing; Wu, Haidi; Wang, Zhiyong; Ware, Robert S; Xiong, Yaqing; Xu, Fei
Abstract : Objectives: Highly efficient diabetes management programs are needed for tackling diabetes in China. This study aimed to assess the effectiveness of a clinic-based intensified diabetes management model (C-IDM) in Mainland China. Research design and methods: A 2-year clinic-based randomized controlled trial was conducted among patients with type 2 diabetes in Nanjing, China. The C-IDM intervention components comprised four domains (disease targeting management, express referral channel, expert visit, patients' self-management) and an integrated running system (disease control centers, general hospitals and local clinics). Control group participants received their usual care, while intervention participants received both the C-IDM package and the usual services. The primary outcome variable was change of hemoglobin A1c (HbA1c). Mixed-effects models were used to compute effect estimates and 95% CI with consideration of both individual and cluster-level confounders. Results: Overall, 1095 of 1143 participants were assessed at study completion. The mean change in HbA1c was significantly greater in the intervention group than in the control group (mean difference (MD)=−0.57, 95% CI −0.79 to –0.36). Similar results were observed for change in body mass index (MD=−0.29, 95% CI −0.49 to –0.10). Participants in the intervention group were more likely to achieve normal HbA1c and body weight compared with their counterparts in control group after adjusting for potentially confounding variables (adjusted OR=1.94, 95% CI 1.35 to 2.81 and 1.79, 95% CI 1.13 to 2.85, respectively). Conclusions: The C-IDM model is feasible and effective in large-scale management of patients with type 2 diabetes in China. It has public health implications for tackling the burden of diabetes in China. Trial registration number: ChiCTR-IOR-15006019.